Promising Natural Products in New Drug Design, Development, and Therapy for Skin Disorders: An Overview of Scientific Evidence and Understanding Their Mechanism of Action - Mohd Zaid NA; Sekar M; Bonam SR; Gan SH; Lum PT; Begum MY; Mat Rani NNI; Vaijanathappa J; Wu YS; Subramaniyan V; Fuloria NK; Fuloria S (Dove Medical Press, 2022)
Nurul Amirah Mohd Zaid,1,* Mahendran Sekar,1,* Srinivasa Reddy Bonam,2,* Siew Hua Gan,3 Pei Teng Lum,1 M Yasmin Begum,4 Nur Najihah Izzati Mat Rani,5 Jaishree Vaijanathappa,6 Yuan Seng Wu,7,8 Vetriselvan Subramaniyan,9 Neeraj Kumar Fuloria,10 Shivkanya Fuloria10 1Department of Pharmaceutical Chemistry, Faculty of Pharmacy and Health Sciences, Royal College of Medicine Perak, Universiti Kuala Lumpur, Ipoh, 30450, Malaysia; 2Institut National de la Santé et de la Recherche Médicale; Centre de Recherche des Cordeliers, Equipe-Immunopathologie et Immunointervention Thérapeutique, Sorbonne Université, Université de Paris, Paris, France; 3School of Pharmacy, Monash University Malaysia, Selangor Darul Ehsan, 47500, Malaysia; 4Department of Pharmaceutics, College of Pharmacy, King Khalid University (KKU), Asir-Abha, 61421, Saudi Arabia; 5Faculty of Pharmacy and Health Sciences, Royal College of Medicine Perak, Universiti Kuala Lumpur, Ipoh, 30450, Malaysia; 6Faculty of Life Sciences, JSS Academy of Higher Education and Research Mauritius, Vacoas-Phoenix, Mauritius; 7Centre for Virus and Vaccine Research, School of Medical and Life Sciences, Sunway University, Selangor, 47500, Malaysia; 8Department of Biological Sciences, School of Medical and Life Sciences, Sunway University, Selangor, 47500, Malaysia; 9Faculty of Medicine, Bioscience and Nursing, MAHSA University, Selangor, 42610, Malaysia; 10Faculty of Pharmacy, AIMST University, Kedah, 08100, Malaysia*These authors contributed equally to this workCorrespondence: Mahendran SekarDepartment of Pharmaceutical Chemistry, Faculty of Pharmacy and Health Sciences, Royal College of Medicine Perak, Universiti Kuala Lumpur, Ipoh, 30450, Perak, MalaysiaTel +6016 - 3346653Fax +605 - 2536634Email mahendransekar@unikl.edu.myAbstract: The skin is the largest organ in the human body, composed of the epidermis and the dermis. It provides protection and acts as a barrier against external menaces like allergens, chemicals, systemic toxicity, and infectious organisms. Skin disorders like cancer, dermatitis, psoriasis, wounds, skin aging, acne, and skin infection occur frequently and can impact human life. According to a growing body of evidence, several studies have reported that natural products have the potential for treating skin disorders. Building on this information, this review provides brief information about the action of the most important in vitro and in vivo research on the use of ten selected natural products in inflammatory, neoplastic, and infectious skin disorders and their mechanisms that have been reported to date. The related studies and articles were searched from several databases, including PubMed, Google, Google Scholar, and ScienceDirect. Ten natural products that have been reported widely on skin disorders were reviewed in this study, with most showing anti-inflammatory, antioxidant, anti-microbial, and anti-cancer effects as the main therapeutic actions. Overall, most of the natural products reported in this review can reduce and suppress inflammatory markers, like tumor necrosis factor-alpha (TNF-α), scavenge reactive oxygen species (ROS), induce cancer cell death through apoptosis, and prevent bacteria, fungal, and virus infections indicating their potentials. This review also highlighted the challenges and opportunities of natural products in transdermal/topical delivery systems and their safety considerations for skin disorders. Our findings indicated that natural products might be a low-cost, well-tolerated, and safe treatment for skin diseases. However, a larger number of clinical trials are required to validate these findings. Natural products in combination with modern drugs, as well as the development of novel delivery mechanisms, represent a very promising area for future drug discovery of these natural leads against skin disorders.Keywords: natural products, skin disorder, dermatitis, psoriasis, skin cancer, anti-inflammatory, drug delivery